완전 무치악 환자에서 하악 임플란트 지지 피개의치 사용 후의 환자만족도에 관한 전향적 연구 - 홍주희; 정겨운; 신상완; 방은경; Hong, Ju-Hee; Jung, Gyu-Un; Shin, Sang-Wan; Pang, Eun-Kyoung (Taehan Chikwa Poch'ol Hakhoe chi, 2015)
Purpose: The purpose of this prospective study was to compare the satisfaction levels of the patients worn implant supported mandibular overdentures and conventional complete dentures. Materials and methods: Full edentulous patients (n=40) who were planned to do implant supported mandibular overdentures, aged 51 to 82 years, were enrolled in this study. All subjects rated their satisfaction levels (mastication, pronunciation, esthetics, pain, and general satisfaction) of their original conventional dentures prior to treatment and their new overdentures 1 week and 12 weeks after the delivery on 10 cm visual analogue scales. Repeated-measures ANOVA was performed to compare the satisfaction level of each three period (P<.05). Results: The mean satisfaction levels of the implant supported overdentures after 1 week and 12 weeks of delivery were significantly higher than those of the conventional complete dentures in all scoring parameters (P<.05). After 12 weeks of overdenture delivery, the increase of the satisfaction levels in mastication, pronunciation, and pain and the decrease in esthetics and general satisfaction were observed in comparison with those after 1 week of delivery, however, no significant difference was found between the satisfaction levels of 1 week and 12 weeks after delivery. Conclusion: An implant supported overdenture might be one of the effective ways to give more satisfaction to patients who were not gratified with a conventional denture and eventually to improve their quality of life. 목적: 이 연구의 목적은 하악 임플란트 지지 피개의치와 전통적인 총의치의 환자 만족도를 비교하기 위함이다. 재료 및 방법: 하악 임플란트 지지 피개의치 치료가 계획된 40명의 상하악 완전 무치악 환자(51세 - 82세)를 대상으로 하였고, 모든 환자는 저작기능, 발음, 심미, 통증, 전반적인 만족도를 기존의 총의치 장착 시와 임플란트 지지 피개의치 장착 1주 후, 12주 후에 visual analog scale법을 이용하여 답하였다. 각 시기의 만족도 비교를 위해 반복측정 분산분석(repeated-measures ANOVA)을 시행하였다(P<.05). 결과: 모든 설문 항목에서 임플란트 지지 피개의치 장착 1주 후, 12주 후에 총의치를 장착했을 때보다 높은 만족도를 보였다(P<.05). 임플란트 지지 피개의치 장착 12주 후에 저작기능, 발음, 통증, 전반적인 만족도는 장착 1주 후에 비해 증가된 결과를 보였고, 심미에 대한 만족도와 전체적인 만족도는 감소함을 나타냈으나, 통계적인 유의성을 보이지는 않았다. 결론: 임플란트 지지 피개의치는 기존의 총의치에 만족하지 못하는 환자들의 만족도를 높임으로써 환자의 삶의 질을 개선시킬 수 있는 효과적인 치료 방법 중 하나가 될 수 있으리라 생각된다.